Pharmacokinetics of tulathromycin after subcutaneous injection in North American bison (Bison bison). Issue 5 (15th March 2015) - Bachtold, K.; Alcorn, J.; Matus, J.; Boison, J.; Woodbury, M.
<x xml:space="preserve">Abstract</x> Tulathromycin is approved for the treatment of respiratory disease in cattle and swine. It is intended for long‐acting, single‐dose injection therapy (Draxxin), making it particularly desirable for use in bison due to the difficulty in handling and ease of creating stress in these animals. The pharmacokinetic properties of tulathromycin in bison were investigated. Ten wood bison received a single 2.5 mg/kg subcutaneous injection of Draxxin. Serum concentrations were measured by liquid chromatography–mass spectrometry (LC‐MS) detection. Tulathromycin demonstrated early maximal serum concentrations, extensive distribution, and slow elimination characteristics. The mean maximum serum concentration (Cmax) was 195 ng/mL at 1.04 h (tmax) postinjection. The mean area under the serum concentration–time curve, extrapolated to infinity (AUC0–inf), was 9341 ng·h/mL. The mean apparent volume of distribution (Vd/F) and clearance (Cls/F) was 111 L/kg and 0.4 L/h/kg, respectively, and the mean half‐life (t1/2) was 214 h (8.9 days). Compared to values for cattle, Cmax and AUC0–inf were lower in bison, while the Vd/F was larger and the t1/2 longer. Tissue distribution and clinical efficacy studies in bison are needed to confirm the purported extensive distribution of tulathromycin into lung tissue and to determine whether a 2.5 mg/kg subcutaneous dosage is adequate for bison.